Development and Prospect of Nanoarchitectured Solar Cells - Bo Zhang; Wenxu Xie; Yong Xiang (International Journal of Photoenergy)
This paper gives an overview of the development and prospect of nanotechnologies utilized in the solar cell applications. Even though it is not clearly pointed out, nanostructures indeed have been used in the fabrication of conventional solar cells for a long time. However, in those circumstances, only very limited benefits of nanostructures have been used to improve cell performance. During the last decade, the development of the photovoltaic device theory and nanofabrication technology enables studies of more complex nanostructured solar cells with higher conversion efficiency and lower production cost. The fundamental principles and important features of these advanced solar cell designs are systematically reviewed and summarized in this paper, with a focus on the function and role of nanostructures and the key factors affecting device performance. Among various nanostructures, special attention is given to those relying on quantum effect.